Silicon attenuates calcium deficiency in rocket plants by increasing the production of non-enzymatic antioxidants compounds - da Silva, Dalila Lopes [UNESP]; Prado, Renato de Mello [UNESP]; Tenesaca, Luis Felipe Lata [UNESP]; da Silva, José Lucas Farias [UNESP]; Mattiuz, Ben-Hur [UNESP] (Elsevier, 2021)
Silicon (Si) might be an alternative to mitigate biological damages caused by calcium (Ca) deficiency in rocket plants (Eruca sativa Miller); however, the mechanisms involved in the use of Si by this species remain unknown. The aim of this study was to evaluate if Si supplementation in a nutrient solution increases antioxidant defenses and mitigate negative effects of Ca deficiency in rocket plants. The experiment was carried out in a greenhouse in a factorial design 2 × 2, being the first factor the supply of a nutrient solution containing low (0.75 mM) or high (5 mM) Ca concentration, aiming to induce either a deficiency or sufficiency of this nutrient, and the second factor the absence or presence of Si (2.5 mM). Ca deficiency resulted in oxidative stress in the plants, by increasing the cell electrolyte leakage index and the content of oxidizing compounds, and decreasing dry matter productivity and quality. Si supplementation through a nutrient solution, under Ca deficiency, has decreased the cell leakage index and increased the content of ascorbic acid, total phenols, carotenoids, the quantum efficiency of the photosystem II, and both fresh and dry matter productions. Similar benefits were also verified in plants under Ca sufficiency. Therefore, Si supplementation is recommended through a nutrient solution, in order to improve quality and increase its productivity after leaf harvesting in rocket plants.
Keywords: Beneficial element; Eruca sativa; Nutritional stress; Oxidative stress; Post-harvest